SIMULASI NUMERIS TIGA DIMENSI KANTONG LUMPUR BENDUNG SAPON - Nindito, Dwi Anung; Istiarto, Istiarto; Kironoto, Bambang Agus (Civil Engineering Forum Teknik Sipil, 2008)
The success factor of a settling basin planning is the trap efficiency. In reality, it is difficult to create a detailed physical model of the sedimentation process. In a more detailed way, sedimentation process phenomena can be formulized by using mathematical equation, for this matter numerical simulation is selected to observe the settling basin performance. A three-dimensional numerical model from SSIIMWin 1.1 is used to carry out this settling basin simulation of the Sapon weir planning. The trap efficiency of the sedimentation process is observed in two different situations: at the time when the settling basin is empty and when it is full. During the empty situation, the velocity and the initial trap efficiency process is measured. When the settling basin is full, inspection is performed to check whether the sedimentation trap process remains effective. The trap efficiency depends on the characteristics of the inflowing sediment (fall velocity of the particle) and the water flow characteristic in the settling basin (flow velocity). Flow velocity simulation is demonstrated using a three-dimensional velocity vectors. Velocity distribution simulation indicates that the value of the horizontal flow velocity component from the upstream to the downstream (augmentation of x/b value) is decreased. The minimum horizontal flow velocity occurs in locations close to the bottom of the bed channel and increasing towards z/h to the surface water. Approaching the wall, the horizontal flow velocity is decreasing and reaches it’s maximum at y/B=0.5. The flow vertical velocity component indicates that approaching the bed channel, the vertical velocity is increasing. The lateral flow velocity component indicates a velocity increase at the horizontal expansion. A three-dimensional vortex occurs on the inlet of the settling basin, due to the vertical expansion. The vortex does not exist in the middle location of the settling basin. Another vortex occurs at the bottom of the channel approaching the downstream of the settling basin. The profile of sediment concentration distribution indicates an increase from the water surface to the bottom (bed channel). The sediment concentration is decreased in quantity to the downstream of the channel. The ratio of the incoming sediment that is deposited (trapped) and inflow the sediment mass entering a settling basin is 69,85 % for the upper 0.06 mm diameter particles. Volume changes of the pond, due to the deposit sediment volume, have lead to a decline in the trap efficiency process. When the volume of the sediments reaches a percentage of 71,84 % of the total pond volume, the settling basin is considered ineffective in performing sedimentation trap process.